Pengaruh cuaca terhadap penyebaran kes demam denggi di Kuala Lumpur / Sholehah Ismail - Sholehah, Ismail (2017)
Weather factor such as temperature, humidity and rainfall, influences Aedes larvae density and spreading of dengue fever cases. Therefore the aim of this research was to study the connection between the effects of weather on the spread of the dengue fever (DF) cases in the federal territory of Kuala Lumpur. The weather factors taken into account in this research is the total rainfall, the average rainfall per year , mean temperature and relative humidity. The term Lag1 is used to indicate a 10 day interval whereas Lag2 is to indicate the interval of 20 days after the actual date of the weather condition recorded. A total of 12 research stations and 2,160 containers of “Mosquito Larvae Trapping Device” (MLTD) has been used to compile the data on the total mosquito larvae collected in the epidemic case areas and the non epidemic areas. The Pearson Correlation Method is used to study the connection between the total larvae with the weather and the DF cases, and the connection between the dengue cases with the weather. This result of this research shows that there is a strong positive correlation between the total larvae in the non-epidemic case areas and the epidemic case areas. This research also finds that there is a strong positive correlation between the total larvae and the weather (rainfall lag2) for the epidemic case area Cheras and Setapak, moderately strong correlation between total larvae and the weather (rainfall lag2) for the epidemic case area City Centre and Kepong, non-epidemic case area Cheras and Damansara. A weak correlation between total larvae and the weather (rainfall lag2) for epidemic case area Damansara and Jalan Klang Lama, non-epidemic case area Kepong, Setapak, City Centre and Jalan Klang Lama. Results of the research also shows that there is no correlation between the weather and the DF case and there is no correlation between the total of larvae and the DF case. Average rainfall per month is also taken into account in finding out the connection between the distribution pattern and the DF case to evaluate the distribution pattern of the dengue case, the Average Nearest Neighbor (ANN) analysis is used together with the V9.3 ESRI ArcGIS analysis programme. The data is processed and converted into a Geography Information System (GIS) format. Results show that in 2009, the distribute pattern indicated that the spread of the DF cases in terms of space in Kuala Lumpur is clustered. However, after the distribution pattern is analysed according to the monthly evaluation of the health zones for the KL federal territory, there are two distinct distribution patterns which are clustered between April to June and scattered between August to November. Therefore, the monthly mean rainfall is not affected by the distribution pattern of the DF cases. From this research it is found that the distribution pattern of the DF cases in Kuala Lumpur in 2009 is spread in terms of space (in scattered and clustered patterns) and the DF cases do not occur at random. This makes it difficult to impose control measures on the scattered pattern as compared to the clustered pattern. Although the correlations are not significant, this research indicates that there is a strong positive correlation between the total larvae in the non-epidemic case areas and the epidemic case areas. This research also finds that there is a strong positive correlation between the total larvae and the weather.